Identification indexes and diagrams for natural gas origin: Connotation, significance and application - Ping’an PENG; Dujie HOU; TENGER; Yunyan NI; Deyu GONG; Xiaoqi WU; Ziqi FENG; Guoyi HU; Shipeng HUANG; Cong YU; Fengrong LIAO (Petroleum Exploration and Development)
Accurate identification of natural gas origin is fundamental to the theoretical research on natural gas geosciences and the exploration deployment and resource potential assessment of oil and gas. Since the 1970s, Academician Dai Jinxing has developed a comprehensive system for natural gas origin determination, grounded in geochemical theory and practice, and based on the integrated analysis of stable isotopic compositions, molecular composition, light hydrocarbon fingerprints, and geological context. This paper systematically reviews the core framework established by him and his team according to related references and application results, focusing on the conceptual design and technical pathways of key diagnostic diagrams such as δ13C1–C1/(C2+C3), δ13C1–δ13C2–δ13C3, δ13CCO2 versus CO2 content, and the C7 light hydrocarbon ternary plot. We evaluate the applicability and innovation of these tools in distinguishing between oil-type gas, coal-derived gas, microbial gas, and abiogenic gas, as well as in identifying mixed-source gases and multi-stage charging systems. The findings suggest that this identification system has significantly advanced natural gas geochemical interpretation in China, shifting from single-indicator analyses to multi-parameter integration and from qualitative assessments to systematic graphical identification, and has also exerted considerable influence on international research in natural gas geochemistry. The structured overview of the development trajectory of natural gas origin discrimination methodologies provides a technical support for natural gas geological theory and practice and offer a scientific foundation for the academic evaluation and application of related achievements.